Excreta disposal in Costa Rica: from the Millennial Development Goals to the Sustainable Development Goals - Mora -Alvarado, Darner Adrián (2019)
The transition from the Millennium Development Goals (DMG) to the Sustainable Development Goals (SDG) caused changes in key concepts about sanitation. In this work, the replacement of the Improved Sanitation Facilities by the Safely managed sanitation services was studied. Septic tanks were analyzed using two scenarios according to the SDG. A comparison between Costa Rica and the world within the context of sanitation was made. Evaluation of excreta disposal and sanitation goals to 2030 for Costa Rica, were evaluated using data from the WHO and the National Water Laboratory (LNA). Results showed that, in the scenario where septic tanks are considered Safely Managed sanitation services, the country reaches 87,6% of the population covered. While when they are not considered as Safely managed sanitation services, a 13% coverage is achieved. Costa Rica reach the fifth position in coverage of basic hygiene between 13 countries of Latin-American. A strict monitoring of public policies related to sanitation is necessary in order to improve the country’s indicators in the context of the SDGs.